2021
DOI: 10.1186/s13046-021-02067-6
|View full text |Cite
|
Sign up to set email alerts
|

SCD1, autophagy and cancer: implications for therapy

Abstract: Background Autophagy is an intracellular degradation system that removes unnecessary or dysfunctional components and recycles them for other cellular functions. Over the years, a mutual regulation between lipid metabolism and autophagy has been uncovered. Methods This is a narrative review discussing the connection between SCD1 and the autophagic process, along with the modality through which this crosstalk can be exploited for therapeutic purposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 131 publications
2
63
0
Order By: Relevance
“…Both LC3 and p62 exhibit enhanced expression and degradation upon autophagy induction, and, thus, our observations can result from decreased or increased autophagic flux 108 . This balance might also provide a rational for seemingly contradictory findings on MUFA supplementation and SCD1 inhibition, which have been proposed to either increase or decrease the autophagic flux 109 . Interestingly, Ppp2ca forms a complex with B55α and dephosphorylates ULK1 (S637) 42 , which might explain the autophagy-regulatory activity of PI(18:1/18:1) under cytotoxic stress.…”
Section: Discussionmentioning
confidence: 92%
“…Both LC3 and p62 exhibit enhanced expression and degradation upon autophagy induction, and, thus, our observations can result from decreased or increased autophagic flux 108 . This balance might also provide a rational for seemingly contradictory findings on MUFA supplementation and SCD1 inhibition, which have been proposed to either increase or decrease the autophagic flux 109 . Interestingly, Ppp2ca forms a complex with B55α and dephosphorylates ULK1 (S637) 42 , which might explain the autophagy-regulatory activity of PI(18:1/18:1) under cytotoxic stress.…”
Section: Discussionmentioning
confidence: 92%
“…The SCD1 gene that encodes the enzymatic protein designated as stearoyl CoA desaturase 1 is proven to be associated with the lipid metabolism of the cell by biocatalyzing the synthesis of monosaturated fatty acids (MUFAs) from precursors that are saturated fatty acids (SFAs) [ 43 ]. This contributes to the synthesis of the basic components of biological membranes, and signaling molecules and provides a source of energy needed for the functioning of the cell [ 43 ]. Research also shows that the SCD1 gene is related to the positive regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that its overexpression is related to the proliferation of neoplastic cells and metastasis. Furthermore, the positive regulation of the autophagy process does not occur in all types of neoplasms [ 43 ]. For example, the transcriptional repression of the SCD1 gene in human hepatocellular carcinoma (HCC) cells was brought about the activation of the apoptosis processes induced by autophagy [ 43 ], and this increased the expression of SCD1 gene in these cells, leading to a worse prognosis for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning the stearoyl-CoA desaturase 1 (SCD1) enzyme as another rate-limiting enzyme in fatty acid synthesis that converts saturated acids to monounsaturated fatty acids (MUFAs) involved in many biological processes (are major constituent of biological structures such as membranes and can also function as or modify signaling molecules). Accordingly more and more studies highlight different roles of SCD1 like modulation of autophagy ( 196 ) others discussing the involvements of SCD1 in regulation of cancer stem cells ( 197 ) and in the promotion of cancer cell proliferation, migration and metastasis ( 198 ). Cancer cells presenting with high degree of membrane saturation are known to be less sensitive to oxidative stress induced by agents like ACs.…”
Section: Lipid Metabolismmentioning
confidence: 99%